Determinants and long‐term costs of early reproduction in males of a long‐lived polygynous mammal. Issue 11 (8th April 2021) - Ritchot, Yanny; Festa‐Bianchet, Marco; Coltman, David; Pelletier, Fanie
Abstract: In long‐lived polygynous species, male reproductive success is often monopolized by a few mature dominant individuals. Young males are generally too small to be dominant and may employ alternative tactics; however, little is known about the determinants of reproductive success for young males. Understanding the causes and consequences of variability in early reproductive success may be crucial to assess the strength of sexual selection and possible long‐term trade‐offs among life‐history traits. Selective pressures driven by fluctuating environmental conditions may depend on age class. We evaluated the determinants of reproduction in male bighorn sheep ( Ovis canadensis ) aged 2–4 years using 30 years of individual‐level data. These young males cannot defend estrous ewes and use alternative mating tactics. We also investigated how the age of first detected reproduction was correlated to lifetime reproductive success and longevity. We found that reproductive success of males aged 3 years was positively correlated to body mass, to the proportion of males aged 2–4 years in the competitor pool, and to the number of females available per adult male. These results suggest that reproductive success depends on both competitive ability and population age–sex structure. None of these variables, however, had significant effects on the reproductive success of males aged 2 or 4 years. Known reproduction before the age of five increased lifetime reproductive success but decreased longevity, suggesting a long‐term survival cost of early reproduction. Our analyses reveal that both individual‐level phenotypic and population‐level demographic variables influence reproductive success by young males and provide a rare assessment of fitness trade‐offs in wild polygynous males. Abstract : Little is known about the determinants of reproductive success for young polygynous male mammals, although the causes and consequences of variability in early reproductive success may be crucial to assess the strength of sexual selection and possible long‐term trade‐offs among life‐history traits. We evaluated the determinants of reproduction in male bighorn sheep ( Ovis canadensis ) aged 2–4 years using 30 years of individual‐level data and investigated how the age of first reproduction was correlated to lifetime reproductive success and longevity. Early reproductive success was influenced by phenotypical and demographical variables, and males that first reproduced at early ages had higher lifetime reproductive success and shorter lifespan, suggesting a long‐term survival cost of early reproduction.